Efficacy and safety of Saccharomyces boulardii as an adjuvant therapy for the eradication of Helicobacter pylori: a meta-analysis - Li, Manning; Xie, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHelicobacter pylori (H. pylori) is highly prevalent worldwide and is closely associated with many gastric conditions. Current methods for eradicating H. pylori include triple or quadruple therapy, including antibiotics, proton pump inhibitors, and bismuth agents; however, with antibiotic abuse and increased drug resistance rates, the effectiveness of traditional methods is gradually decreasing, with many adverse effects such as abdominal pain, diarrhea, and intolerance. In recent years, there has been controversy regarding whether adding Saccharomyces boulardii (S. boulardii) to traditional therapies is beneficial for eradicating H. pylori.AimTo evaluate the efficacy and safety of S. boulardii as an adjuvant therapy for the eradication of H. pylori.MethodsWe systematically searched the PubMed and Web of Science databases from January 2002 to January 2023. The primary outcome was the H. pylori eradication rate. The secondary outcomes included total adverse effects, abdominal pain, diarrhea, bloating, constipation, nausea, vomiting, taste disorders, and other adverse reactions. We evaluated the included studies for publication bias and heterogeneity. Fixed- and random-effects models were used for studies without and with heterogeneity, respectively, to calculate the risk ratios (RRs) and conduct sensitivity and subgroup analyses.ResultsNineteen studies comprising 5,036 cases of H. pylori infection were included in this meta-analysis. The addition of S. boulardii to traditional therapy significantly improved the H. pylori eradication rate [RR=1.11, 95% confidence interval (CI): 1.08–1.15] and reduced the incidence of total adverse effects (RR=0.49, 95% CI: 0.37–0.66), diarrhea (RR=0.36, 95% CI: 0.26–0.48), abdominal distension (RR=0.49, 95% CI: 0.33–0.72), constipation (RR=0.38, 95% CI: 0.26–0.57), and nausea (RR=0.50, 95% CI: 0.37–0.68). However, it did not reduce the occurrence of abdominal pain, vomiting, or taste disorders.ConclusionsS. boulardii supplementation in traditional eradication therapy significantly improves the H. pylori eradication rate and reduces the total adverse effects and incidence of diarrhea, bloating, constipation, and nausea.Systematic review registrationProspero, identifier CRD42024549780.